Silk fibroin micro-particle scaffolds with superior compression modulus and slow bioresorption for effective bone regeneration - Nisal, Anuya; Sayyad, Raeesa; Dhavale, Prachi; Khude, Bhakti; Deshpande, Rucha; Mapare, Vidhyashri; Shukla, Swati; Venugopalan, Premnath (Scientific Reports, 2018)
Silk fibroin (SF), a natural polymer produced by Bombyx mori silkworms, has been extensively explored to prepare porous scaffolds for tissue engineering applications. Here, we demonstrate, a scaffold made of SF, which exhibits compression modulus comparable to natural cancellous bone while retaining the appropriate porosities and interconnected pore architecture. The scaffolds also exhibit high resistance to in-vitro proteolytic degradation due to the dominant beta sheet conformation of the SF protein. Additionally, the scaffolds are prepared using a simple method of microparticle aggregation. We also demonstrate, for the first time, a method to prepare SF micro-particles using a Hexafluoroisopropanol-Methanol solvent-coagulant combination. SF microparticles obtained using this method are monodisperse, spherical, non-porous and extremely crystalline. These micro-particles have been further aggregated together to form a 3D scaffold. The aggregation is achieved by random packing of these microparticles and fusing them together using a dilute SF solution. Preliminary in-vitro cell culture and in-vivo implantation studies demonstrate that the scaffolds are biocompatible and they exhibit the appropriate early markers, making them promising candidates for bone regeneration.

Silk fibroin and ceramic scaffolds: comparative in vitro studies for bone regeneration - Deshpande, Rucha; Shukla, Swati; Sayyad, Raeesa; Salunke, Shalmali; Nisal, Anuya; Venugopalan, Premnath (Bioengineering & Translational Medicine, 2021)
Synthetic bone void fillers based on calcium ceramics are used to fill cavities in the bone and promote bone regeneration. More recently, silk fibroin (SF), a protein polymer obtained from Bombyx mori silkworm, has emerged as a promising material in bone void filling. In this work, we have compared the safety and efficacy of two types of silk fibroin-based bone void fillers with currently used and commercially available ceramic bone void fillers (based on calcium sulphate, beta tricalcium phosphate, and beta tricalcium phosphate with hydroxyapatite). Further, we have also evaluated these two types of SF scaffolds, which have strikingly different structural attributes. The biocompatibility of these scaffolds was comparable as assessed by cytotoxicity assay, cellular adhesion assay, and immunogenic assay. Ability of the scaffolds to support differentiation of human mesenchymal stem cells (hMSCs) into an osteoblastic lineage was also evaluated in an in vitro differentiation experiment using reverse transcriptase polymerase chain reaction analysis. These results revealed that cells cultured on SF scaffolds exhibit higher expression of early to late markers such as Runx2, BMPs, collagen, osterix, osteopontin, and osteocalcin as compared with ceramic-based scaffolds. This observation was further validated by studying the expression of alkaline phosphatase and calcium deposition. We also show that scaffolds made from same material of SF, but characterized by very different pore architectures, have diverse outcome in stem cell differentiation.
Keywords: beta tricalcium phosphate; bone regeneration; bone void filler; calcium sulphate; hMSCs; hydroxyapatite; osteoblasts; scaffold; Silk fibroin

Engineered silk matrix as a substitute for acellular dermal matrix in breast reconstruction surgery - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Sayyad, Raeesa; Kewale, Bhawana; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (International Journal of Biological Macromolecules, 2025)
Implant-based breast reconstruction is a common standard of care for breast cancer patients following mastectomy. To support implant weight and placement, surgeons utilize autologous tissues, acellular dermal matrices (ADMs), or synthetic meshes. While ADMs provide structural support, they present significant risks, including infection transmission and seroma. Conversely, synthetic meshes exhibit poor cellular adhesion, leading to inadequate tissue integration. To address these challenges, there is a need for a matrix that enhances tissue integration while minimizing infection risks and other complications. Silk fibroin (SF), a natural biopolymer, possesses excellent biocompatibility and mechanical properties. This study introduces a novel engineered silk matrix (ESM) as an advanced solution for soft tissue regeneration, specifically in breast reconstruction surgery. The present study establishes the safety of ESM and evaluates its potential a tissue regeneration matrix through extensive in-vitro and in-vivo analyses. In-vitro assays demonstrated superior cellular adhesion, proliferation of human mammary fibroblast cells (HMFCs), collagen deposition and angiogenesis in ESM compared to collagen matrices and ADMs. Safety assessments, conducted in accordance with ISO 10993 guidelines, confirmed noncytotoxic nature of ESM. Furthermore, subcutaneous implantation revealed no systemic toxicity or adverse tissue reactions. In-vivo studies utilizing a Yorkshire pig model of simulated breast reconstruction surgery, demonstrated superior performance of ESM over collagen matrices in tissue regeneration. The findings showed enhanced fibroblast density, increased collagen deposition, and improved vascularization. These results suggest that ESM is a safer and more effective alternative to ADMs in breast reconstruction, with the potential to revolutionize post-mastectomy care for breast cancer patients.
Keywords: Biocompatibility; Breast reconstruction; ISO 10993; Polymer; Safety; Silk protein; tissue regeneration

Engineered silk-dressing for acceleratedwound healing: biocompatibility and efficacy studies - Deshpande, Rucha; Pillai, Lakshmi R.; Sayyad, Raeesa; Shukla, Swati; Nisal, Anuya; Venugopalan, Premnath (Macromolecular Bioscience, 2025)
Advanced wound care dressings are essential for improving clinical outcomes. The present study investigates the wound management potential of a unique dressing fabricated from silk proteins. The dressing was characterized for its physical and structural properties, including surface texture, porosity, fluid absorption capacity, and moisture vapor transmission rate. These parameters have been found to be critical for optimal wound healing. In vivo full thickness wound healing studies in a rat model validated the efficacy of the Silk-dressing compared to conventional cotton gauze and commercial polyurethane foam dressings. Histopathological analysis confirmed improved re-epithelialization, collagen deposition, angiogenesis, and formation of secondary follicles. Key advantages of Silk-dressing included non-adherence, absorption of exudate, maintenance of optimal moisture at wound site and acceleratedwound closure. Biocompatibility studies were also conducted in accordance with ISO 10993 guidelines, demonstrating no cytotoxicity, irritation, sensitization, or pyrogenicity. These findings highlight the potential of this uniquely designed Silk-dressing as a superior alternative for wound management, with a potential to improve clinical outcomes.
Keywords: Biocompatibility; biopolymer; ISO 10993; Silk protein; wound Healing